Indirect plant regeneration in aromatic rice (Oryza sativa L.) var. ‘Kalijira’ and ‘Chinigura’ - Mohammad Abdul MANNAN; Tushar Chandra SARKER; Mst. Towhida AKHTER; Ahmad Humayan KABIR; Mohammad Firoz ALAM (Acta Agriculturae Slovenica)
Mature seeds of two traditional rice genotypes (Kalijira and Chinigura) were used for callus induction and plant regeneration on different concentrations and combinations of plant growth regulators cultured on MS (Murashige and Skoog) basal medium. Callus induction frequency was different between the cultivars, as well as among the 2,4-dichlorophenoxyacetic acid (2,4-D) levels tested. Both tested cultivars exhibited highest callus frequency at 2 mgl-1 2,4-D. The incorporation of benzylaminopurine (BAP) and kinetin (KIN) in the callus induction medium supplemented with 2 mgl-1 2,4-D did not significantly improve the callus induction frequency but required days of callus initiation were decreased compared to single use of 2,4-D. After two subcultures, at 21 days interval, embryogenic callus was placed on medium containing different concentration and combination of auxin and cytokinin. Treatment T4 (0.5 mg l-1 BAP and 0.1 mg l-1 IBA) showed the highest shoot induction: 91.67% in Kalijira and 83.33% in Chinigura. Similarly, the highest range of shoot number was also observed in both genotypes when treated with 0.5 mgl-1 BAP and 0.1 mgl-1 IBA. Plant regeneration efficiency was further observed best when treated with 1 mgl-1 2,4-D along with 1 mgl-1 2,4-D along with 1 mgl-1 BAP and 1 mgl-1 IBA. Furthermore, the highest number of callus derived shoot per culture was achieved in 2 mgl-1 2,4-D along with 1 mgl-1  BAP and 1 mgl-1 IBA. Both rice genotypes are promising in terms of callus induction frequency and morphology, and regeneration ability of the embryogenic callus.